Turnover and health selection among foundry workers. - Koskela, Riitta-Sisko; Luoma, Katariina; Hernberg, Sven (Scandinavian Journal of Work, Environment & Health, 1976)
The quantity, reasons, and health selection involved in labor turnover were studied with the use of questionnaires and employers` records. The basic material was the personnel of 20 representative foundries. The turnover in 1950--1972 was estimated from a sample of 588 workers. The causes and health selection were studied with questionnaires put to the 1,789 current employees (91% response), the 493 foundrymen who had left after at least 5 years of exposure (the 5-year-plus men, 71% response) and 424 of those who had left after less than 1 year of exposure (the 1-year-minus men, 55% response). The men were asked to describe their present and earlier work at the foundry, the nature and duration of their exposure, diagnosed lung and heart diseases, and chronic bronchitis and angina pectoris and to assess their present and former state of health and work capacity. The disability analysis was based on a sample of 2,834 men whose data were taken from the Social Insurance Register. The disability findings were compared to expected values based on the Finnish male population. Turnover proved to be rapid; short periods of employment predominated. The major reasons for leaving were poor work conditions, physically demanding work, low pay, and poor health. The turnover was fastest in dusty occupations. Relatively more exfoundrymen, both 5-year-plus and 1-year-minus, than current employees felt their health and/or work capacity to be poor. More of the older men in the 5-year-plus group than men of the same age in the current group had chronic bronchitis and diagnosed lung disorders. Both the 5-year-plus and the 1-year-minus exfoundrymen had relatively more diagnosed heart disorders than did the current employees. The disability prevalences of the foundrymen in any category of diseases did not exceed the expected values based on the male population. The overall findings indicate early health selection prior to pensionable disability and/or death.
Keywords: cohort study; foundry worker; health selection; questionnaire; questionnaire study; retrospective cohort study; turnover